The Relationship Between the Characteristics of Audit Committee Members and Earnings Management Based on UK Evidence - Ning, He (2019)
The effect of personal traits of the audit committee members on reducing the earnings management has been an attractive subject in recent studies while the findings are all mixed and inconclusive. This study focuses on three specific personality traits of the audit committee members: Average age, gender diversity, and financial professional knowledge background. This study investigates whether the earnings management is influenced by those three traits or not and how do they affect each other. The study uses FTSE 100 and 250 firms in the UK for the year 2018 as the sample to examine the relationships and the total sample size is 221 firm-observations. The results show that the female presentation in the audit committee does not bring any effects on earnings management, and it may due to the Brexit impact. Moreover, the findings indicate a significantly negative relationship between the average age of AC members and earnings management, and the financial expertise exhibit the same impact on earnings management. The study then separate the FTSE 100 firms and FTSE 250 firms, and the results show that for the FTSE 100 firms, the average age and financial experts still play significant roles in curbing earnings management while no such impact presents for the FTSE 250 firms; this suggests that the average age of AC members deserves more attention when considering the earnings management. Furthermore, the Brexit impact should be taken into consideration for the firms in the UK, and the policymakers may adjust their strategy and methods on monitoring the audit committee role in the following years.